A Multimodal Analysis In Banner Of COVID-19 - Khalida Rahmadina; Tengku Silvana Sinar; Yulianus Harefa (BAHAS, 2021)
ABSTRACT This will discuss multimodal analysis where there are visual and verbal, This study aims to see changes in the visual function of the WHO banner itself which is conveyed through objects that are following the objectives themselves. In this study, the authors also used a qualitative descriptive approach where all data were analyzed with the theory of Kress and Van Leeuwen (2006). The results of the study show where the visual and verbal processes that occur in this banner. Keywoard : Multimodal Analysis, Verbal & Visual